Approaches to Assessing the Sustainability of Business Development - Danishevich, Danishev Doniyor (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This article conducts a thorough analysis of elements related to the theme of "organizational development sustainability." It primarily explores various methods of assessing this concept and their application in analyzing the impact of strategic initiatives on organizations during the transition to sustainable development. The work begins with a review and analysis of existing theoretical models, definitions, and approaches to the sustainability of organizations. Throughout the analysis, different scientific methods used to study this topic are identified and evaluated, including their merits and limitations. The focus is on exploring alternative scientific methods for defining organizational sustainability, offering a unique author's definition that underscores the complexities in its interpretation. The article emphasizes the need for continued in-depth research in this area, especially in terms of expanding evaluative criteria and parameters. The importance of considering qualitative indicators and diverse aspects of sustainable development is highlighted. The presented analysis and directions for future research can serve as a basis for forming strategies and recommendations for organizations aspiring to sustainable development under modern conditions.